2011
DOI: 10.1111/j.1528-1167.2011.03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging in startle epilepsy: Involvement of a mesial frontoparietal network

Abstract: Purpose: Startle epilepsy is a rare form of epilepsy with seizures triggered by unexpected stimuli. Previous studies have suggested the participation of several brain regions, such as the supplementary motor area (SMA) or the mesial aspect of the frontal and parietal lobes in the generation of startle epilepsy. However, how these brain regions interact with each other during seizures remains largely unknown. The aim of this study was to get insight into brain structures involved in startle-induced seizures usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
2
38
1
1
Order By: Relevance
“…For this patient, the startle stimuli may be amplified in the SSMAs to provoke a startle-induced seizure or disappeared in the SSMAs without abnormal reaction. We believed that other cortices which were not covered by the electrodes, such as the cingulate gyrus and precuneus, were involved in startle seizures [6,10,15]. Based on a study using ictal EEG-fMRI and SPECT coregistered to MRI (SPECT/SISCOM), it was proposed that startle seizures resulted from the interaction of all those regions-mainly from parietofrontal networks-that include the motor/premotor cortex, precuneus and SSMA [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this patient, the startle stimuli may be amplified in the SSMAs to provoke a startle-induced seizure or disappeared in the SSMAs without abnormal reaction. We believed that other cortices which were not covered by the electrodes, such as the cingulate gyrus and precuneus, were involved in startle seizures [6,10,15]. Based on a study using ictal EEG-fMRI and SPECT coregistered to MRI (SPECT/SISCOM), it was proposed that startle seizures resulted from the interaction of all those regions-mainly from parietofrontal networks-that include the motor/premotor cortex, precuneus and SSMA [6].…”
Section: Discussionmentioning
confidence: 99%
“…Onset of the seizures is during childhood or adolescence [3]. The ictal onset zone in startle epilepsy has been attributed to the primary motor cortex, premotor cortex, parietal lobe, peri-insular auditory cortex and the SSMA [4][5][6]. It was reported that most cases of startle epilepsy were associated with structural lesions found on MRI [6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, functional studies with MEG, ictal SPECT and PET support the hypothesis of a large network associated with SISs [6,7]. This epileptic network appears, based on functional neuroimaging studies, to extend beyond the frontal motor/premotor cortex, the primary sensory cortex, and the SMA, constituting to a frontoparietal epileptic network.…”
Section: Discussionmentioning
confidence: 87%
“…Startle-provoked seizures typically arise between the ages of 10 months and 14 years and are seldom diagnosed in adults 13. The presumed insults resulting in startle epilepsy (including hypoxic-ischaemic injury, central nervous system infection and traumatic brain injury) often occur in the perinatal or postnatal period 14.…”
Section: Introductionmentioning
confidence: 99%
“…Startle-provoked seizures typically arise between the ages of 10 months and 14 years and are seldom diagnosed in adults 13. The presumed insults resulting in startle epilepsy (including hypoxic-ischaemic injury, central nervous system infection and traumatic brain injury) often occur in the perinatal or postnatal period 14. Although the exact cerebral structures responsible for the generation of startle-provoked seizures have not been fully elucidated, mesial structures, including the supplementary motor area (SMA), precuneus and primary motor/somatosensory areas, have been suggested by some 1.…”
Section: Introductionmentioning
confidence: 99%